Recovery efficiencies for Burkholderia thailandensis from various aerosol sampling media - Dabisch, Paul; Bower, Kristin; Dorsey, Brandi; Wronka, Loni (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia thailandensis is used in the laboratory as a surrogate of the more virulent B. pseudomallei. Since inhalation is believed to be a natural route of infection for B. pseudomallei, many animal studies with B. pseudomallei and B. thailandensis utilize the inhalation route of exposure. The aim of the present study was to quantify the recovery efficiency of culturable B. thailandensis from several common aerosol sampling devices to ensure that collected microorganisms could be reliably recovered post-collection. The sampling devices tested included 25-mm gelatin filters, 25-mm stainless steel disks used in Mercer cascade impactors, and two types of glass impingers. The results demonstrate that while several processing methods tested resulted in significantly lower physical recovery efficiencies than other methods, it was possible to obtain culturable recovery efficiencies for B. thailandensis and physical recovery efficiencies for 1 μm fluorescent spheres of at least 0.95 from all of the sampling media tested given an appropriate sample processing procedure. The results of the present study also demonstrated that the bubbling action of liquid media in all-glass impingers (AGIs) can result in physical loss of material from the collection medium, although additional studies are needed to verify the exact mechanisms involved. Overall, the results of this study demonstrate that the collection mechanism as well as the post-collection processing method can significantly affect the recovery from and retention of culturable microorganisms in sampling media, potentially affecting the calculated airborne concentration and any subsequent estimations of risk or dose derived from such data.